A methodology to downscale water demand data with application to the Andean region (Ecuador, Peru, Bolivia, Chile). Issue 4 (12th March 2021) - Zogheib, Charles; Ochoa-Tocachi, Boris F.; Moulds, Simon; Ossa-Moreno, Juan; Villacis, Marcos; Verano, Carlos; Buytaert, Wouter
ABSTRACT: Mountainous regions are a hotspot for water scarcity and anthropogenic pressure on water resources. Substantial uncertainty surrounds projections of future climate and water availability. Furthermore, quantitative and distributed data on water demand are generally scarce, dispersed, and highly heterogeneous. This forms a major bottleneck to studying water resources issues and developing strategies to improve water resource management. Here we present a methodology to produce and evaluate high-resolution gridded maps of anthropogenic surface water demand with application to the Andean region. These data are disaggregated according to the major types of water demand: domestic users, irrigated area, and hydropower. This dataset was built by homogenizing, integrating, and interpolating data obtained from various national institutions in charge of water resource management as well as relevant global datasets. The maps can be used to research anthropogenic impacts on water resources, and to guide regional decision-making in regions such as the Andes.